Influencia del sistema de trabajo por catálogo en el desarrollo personal y profesional de las consultoras y directoras de la empresa Unique en la provincia de Ascope 2018 - Julca Pérez, Jessica Rosmery (2019)
The present work has been carried out in order to determine the influence that the system of work by catalog has on the personal and professional development of the consultants and directors of the Unique company in the province of Ascope - 2018. The general objective of this research is: Determine what is the influence of the system of work by catalog in the personal and professional development of the consultants and directors of the company Unique in the province of Ascope 2018. To this end the problem formulated for the investigation was: What is the influence of the system of work by catalog in the personal and professional development of the consultants and directors of the company Unique in the province of Ascope - 2018? and it was hypothesized: The system of work by catalog has a direct influence on the personal and professional development of the consultants and directors of the Unique company in the province of Ascope - 2018. There was a study population of 200 people between consultants and directors; and a sample of 80 people. The design of the research used for this non-experimental study was descriptive - transectional. Regarding the technique, the survey was used and the questionnaire was used as an instrument. The result was that the consultants are satisfied with the work system of the company. Also, the conclusion reached was the company manages very well the way to encourage and how to collaborate to personal development as a professional consultants are at a very high level.